Synthesis and characterization og gallium (III) complexes with chalcone and schiff base ligands - Chiau, Shis Hoong (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Synthesis and spectroscopic characterization of gallium(Ill) complexes with chalcone and Schiff base are reported in this thesis. Tautomerization was happening in chalcone before coordinated with gallium(Ill) bromide. For Schiff base compounds, which OH group located in ortho- or puru- substitution, a intramolecular hydrogen bond present between hydrogen atom from phenolic group with nitrogen atom from C:= N group. Reactions of chalcone as well as Schiff base with gallium(Ill) bromide gave a new respective coordination mode of Ga-O bonds. The ligands appear to act as monodentate species in Ga(III) complexes, making gallium atom four-coordinated in tetrahedron structure. The ratio between Ga : ligand is 1: 1 for all the Ga(III) complexes in this research.